It's raining, it's pouring - Eagle, Kin (Boston : Whispering Coyote Press, 1994)
This expanded version of the nursery rhyme "It's raining, it's pouring" shows what happens to the old man in all kinds of weather.
Keywords: Weather-Fiction; Stories in rhyme